Seedlings of Syzygium malaccense (L.) Merr. & L.M. Perry according to temperatures and temperatures - Berto, Thaíse dos Santos; Melo, Luan Danilo Ferreira de Andrade; Melo Junior, João Luciano de Andrade; Crisóstomo, Natália Marinho Silva; Araújo Neto, João Correia de; Ferreira, Vilma Marques (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The market for jambo (Syzygium malaccense (L.) Meer. & L.M. Perry) has grown in recent years, attracting the attention of Brazilian producers, who seek diversification in production and better prices in the fruit trade. Today there is no record of any variety, with most orchards formed by seedlings produced by seeds. Thus, the work aimed to verify the emergence of seedlings of jambo from seeds collected in the soil and in the crown under different temperatures. The work was conducted at the Plant Propagation Laboratory belonging to the Engineering and Agricultural Sciences Campus of the Federal University of Alagoas. A completely randomized experimental design was adopted, in a 2x5 factorial scheme, with two forms of collection (soil and canopy) and five temperatures (20, 25, 30, 35, 20-30 ºC). The evaluated parameters were: water content, first emergency count, emergency, emergency speed index, root and shoot length and seedling dry mass. Jambo seeds from fruits collected in the soil exhibited greater physiological potential.